The Annotated Statutes of Malaysia: companies commission of Malaysia Act 2001 (Act 614) - 2009 issue - Abd Ghadas, Zuhairah Ariff (LexisNexis Malaysia Sdn Bhd, 2009)
Companies Commission of Malaysia Act 2001 (Act 614), 2009 issue (This issue states the law as at 19 June 2009)